2018
DOI: 10.1590/1516-4446-2016-2122
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to violence: associations with psychiatric disorders in Brazilian youth

Abstract: Investment in reducing SES inequalities and preventing violent events during childhood may improve the mental health of youths from low SES backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
2
11
0
2
Order By: Relevance
“…The data found in the present study confirm the findings evidenced in the literature, which indicate a high prevalence of behavioral problems in the Brazilian children and youth population (Anselmi et al, 2004;Borsa et al, 2011;Lopes et al, 2016), as well as the association of these problems with SV (Fatori et al, 2013;Fidalgo et al, 2018). Besides, there are also differences when it comes to the prevalence of certain behavior problems concerning sex and the little difference varying on the age range of the adolescents assessed (Achenbach & Rescorla, 2001).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The data found in the present study confirm the findings evidenced in the literature, which indicate a high prevalence of behavioral problems in the Brazilian children and youth population (Anselmi et al, 2004;Borsa et al, 2011;Lopes et al, 2016), as well as the association of these problems with SV (Fatori et al, 2013;Fidalgo et al, 2018). Besides, there are also differences when it comes to the prevalence of certain behavior problems concerning sex and the little difference varying on the age range of the adolescents assessed (Achenbach & Rescorla, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…It is also observed that the prevalence of externalizing and internalizing problems was numerically equivalent, with 16.4% of adolescents reaching the clinical range for internalizing problems and 15.3% for externalizing problems. In the study by Fidalgo et al (2018), in which the DSM-IV diagnostic criteria were used, violent experiences and low socioeconomic levels were associated with the presence of internalizing and externalizing problems. Thus, it is understood that the SV scenario does not seem to be associated with a specific type of problem, but rather with the existence of emotional and behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 210 students with active phones, 180 consented to participate, generating an acceptance rate of 85%. The other 15% declined to participate 10…”
Section: Methodsmentioning
confidence: 99%
“…That same year, the prevalence of common mental disorders among adolescents (15–19 years) was estimated at 13.2% in the city [ 9 ]. Recent studies in São Paulo show that exposure to violence during childhood and adolescence are significantly associated with mental health problems, especially among individuals in low socioeconomic strata [ 10 ]. In addition, previous global research has demonstrated that adolescent boys have higher community violence exposure than girls [ 11 ], yet girls experience greater anxiety and depression when exposed to community violence than boys [ 12 ].…”
Section: Introductionmentioning
confidence: 99%